The correlation between critical thinking skills and decision-making skills of prospective physics teacher students - Yusal, Yulianti; Nurazmi, Nurazmi (Universitas Muhammadiyah Mataram, 2024)
This research aims to find out the relationship between critical thinking skills and the decision-making skills of prospective physics teacher students. This research is correlational or relationshipal, and it is ex post facto research with a quantitative approach. The population of this study was all first-semester students, totaling 99 students at one of the universities in South Sulawesi. The sample used in this research was 76 students, taken using convenience sampling. The results of the research show that there is a positive correlation between critical thinking skills and the decision-making skills of prospective physics teacher students, with a correlation coefficient (rxy) of 0.549 at a medium level and a coefficient of determination of 30.1%. Thus, if a student's critical thinking skills are high, the higher their decision-making skills, or vice versa, the lower the student's critical thinking skills, the lower their decision-making skills.